THE IMPLEMENTABILITY OF WESTERN APPROACHES IN EASTERN SOCIETIES - Soenjono Dardjowidjojo (Universitas Katolik Indonesia Atma Jaya, 2006)
The field of foreign language teaching has been dominated mostly by Western views. While some of these views can indeed be implemented, many others, especially with regards to the role of the teacher and that of the students, stumble on cultural barriers; the approaches are also constrained by the unavailability of educational facilities in most Eastern societies. This paper is to look into these two constraints: (a) in the case of learner autonomy and the new role of the teacher, the Western concepts cannot be conveniently implemented without changing the cultural values of the society, and (b) in the case of educational facilities, Western approaches such as Community Language Learning, Total Physical Response, Suggestopedy, and Content-based Instruction, which are claimed to be student-centered, cannot easily be implemented in normal classrooms where educational aids are not generally available on the national scope.Keywords: learner autonomy, Community Language Learning, Total Physical Response, Suggestopedy, Content-based Instruction.